Analysis Of Javanese Language Prosody (Acoustic Phonetic Study) - Nidiya Mawarni; Tengku Syarfina; Putri Annisa Zulhantiar; Rahmadsyah Rangkuti (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research aims to analyze the prosody contained in Javanese using an acoustic phonetic approach. This research also uses an instrumental approach, where researchers use the Praat program to analyze the frequency, intensity, and duration of the voices of male and female Javanese speakers. Data were collected from one male Javanese speaker and one female Javanese speaker. The results of the analysis show that the frequency of the voices of male Javanese speakers tends to be lower than that of female Javanese speakers. The intensity of the voices of male Javanese speakers tends to be smaller than that of female Javanese speakers. In contrast to the frequency and intensity, the duration of the male voice is also higher than that of female voices. This research confirms that there are significant differences in vocal characteristics between male and female speakers of Javanese. These results indicate that there are distinctive linguistic patterns between the two genders in the Javanese language community.